Characterization of the Histopathologic Features in Patients in the Early and Late Phases of Cutaneous Leishmaniasis - Saldanha, Maíra G. (Am J Trop Med Hyg, 2017)
Cutaneous leishmaniasis (CL), characterized by an ulcerated lesion, is the most common clinical form of human leishmaniasis. Before the ulcer develops, patients infected with Leishmania (Viannia) braziliensis present a small papule at the site of the sandfly bite, referred to as early cutaneous leishmaniasis (E-CL). Two to four weeks later the typical ulcer develops, which is considered here as late CL (L-CL). Although there is a great deal known about T-cell responses in patients with L-CL, there is little information about the in situ inflammatory response in E-CL. Histological sections of skin biopsies from 15 E-CL and 28 L-CL patients were stained by hematoxilin and eosin to measure the area infiltrated by cells, as well as tissue necrosis. Leishmania braziliensis amastigotes, CD4(+), CD8(+), CD20(+), and CD68(+) cells were identified and quantified by immunohistochemistry. The number of amastigotes in E-CL was higher than in L-CL, and the inflammation area was larger in classical ulcers than in E-CL. There was no relationship between the number of parasites and magnitude of the inflammation area, or with the lesion size. However, there was a direct correlation between the number of macrophages and the lesion size in E-CL, and between the number of macrophages and necrotic area throughout the course of the disease. These positive correlations suggest that macrophages are directly involved in the pathology of L. braziliensis–induced lesions.